Transcriptome profiling reveals potential genes involved in browning of fresh-cut eggplant (Solanum melongena L.) - Xiaohui Liu (Nature Portfolio, 2021)
Abstract Fresh-cut processing promotes enzymatic browning of fresh fruits and vegetables, which negatively affects the product appearance and impacts their nutrition. We used RNA-sequencing to analyze the transcriptomic changes occurring during the browning of fresh-cut eggplant fruit samples from both browning-sensitive and browning-resistant cultivars to investigate the molecular mechanisms involved in browning. A total of 8347 differentially expressed genes were identified, of which 62 genes were from six gene families (i.e., PPO, PAL, POD, CAT, APX, and GST) potentially associated with enzymatic browning. Furthermore, using qRT-PCR, we verified 231 differentially regulated transcription factors in fresh-cut eggplant fruits. The enzyme activities of PPO, POD, PAL, and CAT in ‘36’ were significantly higher than those of ‘F’ fresh-cut for 15 min. Both PPO and POD play a major role in the browning of eggplant pulp and might therefore act synergistically in the browning process. Meanwhile, qPCR results of 18 browning related genes randomly screened in 15 eggplant materials with different browning tolerance showed variant-specific expression of genes. Lastly, gene regulatory networks were constructed to identify the browning-related genes. This work provides a basis for future molecular studies of eggplants, and lays a theoretical foundation for the development of browning-resistant fresh-cut fruits and vegetables.